Community Empowerment Through the Enhancement of Entrepreneurship in the Production of Lotion and Mosquito Spray for Dengue Fever in Sukmajaya, Depok - Prastiwi, Rini; Dewanti, Ema; Rahayu, Dewi Pudji; Ladeska, Vera; Wardani, Elly (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2024)
Dengue fever has become one of the endemic diseases in the Sukmajaya area of Depok. This disease can claim the lives of up to 10% of those affected. Community empowerment, particularly through the empowerment of PKK groups. This community service aims to increase the community's ability to prevent the spread of the Aedes aegypti mosquito through empowering the PKK group community. It can prevent the spread of mosquitoes by introducing natural materials as mosquito repellents and creating lotion and spray products as alternative solutions. The program involves training and assistance in producing lotions and sprays using natural ingredients. Using essential oils as raw materials, along with marketing techniques, can be a solution to address this issue. The Community Service Team of the Faculty of Pharmacy and Science (FFS) UHAMKA and the Faculty of Economics and Business (FEB) UHAMKA provided comprehensive training and guidance in the pharmacy skills program. Participants were instructed on creating lotion and mosquito repellent spray formulations using natural ingredients, including orange leaf extract, orange oil, lavender oil, and clove oil. The training consisted of lectures followed by a hands-on workshop on entrepreneurship, focusing on the importance of selecting appropriate packaging and promoting the products effectively. Participants are very enthusiastic about acquiring this skill because it enhances the capabilities of PKK administrators in utilizing natural materials in forms that will later boost the spirit of entrepreneurship and help prevent dengue fever.